RUSCISM AS A NEW VERSION OF TOTALITARIANISM - Romanyuk, Oleksandr (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2022)
This paper is devoted to clarifying the essence of ruscism as a phenomenon of modern socio-political reality. It is noted that the concept of ruscism appeared in public and scientific circulation as a result of the formation of Putin's regime in Russia, and its spread is connected with the beginning of the full-scale Russian-Ukrainian war. Although this concept has already received its interpretations in the publications of a number of analysts, there is still no complete conceptual understanding of it. The author believes that the conceptual understanding of ruscism should be carried out within the framework of totalitarian studies, since it is a new version of totalitarianism. The idea of ruscism as a simple imitation of fascism and Nazism is refuted. The emphasis is placed on his historical Russian roots.Attention is drawn to the facts that, firstly, Russian statehood originates in the Golden Horde, from which it inherited the despotic character of government and aggressive foreign policy; secondly, Russia has never had long periods of democratic rule in the course of its historical development; thirdly, the first totalitarian regime in the modern world arose precisely in Russia; fourthly, under Stalin, it acquired the greatest totalitarian quality in history. The author emphasizes that ruscism cannot be considered a simple resuscitation of Stalinism, because it arose in the new historical conditions of the development of both Russia and its international environment, which determined its peculiarities.The peculiarities of ruscism as a new version of totalitarianism are that: the creation of a totalitarian party, the formation of a broad totalitarian movement, and the development of a totalitarian doctrine took place already after Putin acquired state power; the Russian political system is formally multi-party; the control of the political regime over the functioning of the economy is carried out not so much by formal state institutions as by Putin's informal clan.